Interdisciplinary homecare improves the mental health dimension of quality of life in diabetic ulcer patients - Wantonoro, Wantonoro; Komarudin, Komarudin; Imania, Dika Rizki; Harun, Sigit (JHeS (Journal of Health Studies), 2023)
The study aimed to identify the effect of interdisciplinary homecare programs on the mental health dimensions of patients' quality of life who require long-term care services. The research method was conducted with a quasi-experiment for six months of intervention on sixteen patients obtained with a random sample for January-September 2022 at the PKU Muhammadiyah Hospital Yogyakarta homecare unit. Short form-36 (SF-36) was used to evaluate the quality of life dimension. Results; Interdisciplinary homecare significantly improves the health of patients with long-term care needs; diabetic ulcers (p=0.001). Age and comorbidities were identified as characteristics of patients with diabetic ulcers, which must be considered in treating diabetic ulcers. Conclusion; Assistance with interdisciplinary home care is recommended in long-term care in community settings and patients to improve the quality of life, especially the mental health of patients.Â